Sustainable Leadership as a Mediating Variable in the Relationship between University Reputation and Organizational Ambidexterity: King Saud University is a Model - Alharazi, Abdulaziz Ahmed (Jazan University Journal of Human Sciences, 2024)
The study aimed to reveal the mediating role of sustainable leadership in the relationship between the university’s reputation and its organizational ambidexterity from the perspective of faculty members at King Saud University. This is done by revealing the degree of practicing the dimensions of sustainable leadership, the degree of achieving the dimensions of organizational reputation, as well as revealing the degree of achieving the dimensions of organizational ambidexterity. Therefore, the study relied on Predictive correlational, and the study sample consisted of (362) university faculty members. The questionnaire was used as a tool for collecting data, and the study reached a number of results, the most prominent of which are: Practicing the dimensions of sustainable leadership resulted in a moderate response rate in general, with a mean of (3.40) and a standard deviation of (0.762). The results of the study also revealed that the dimensions of organizational reputation had a high degree of response, with a mean of (3.49) and a standard deviation of (0.711). The results of the study also found that the dimensions of organizational ambidexterity had a moderate response rate, with an arithmetic mean of (3.32) and a standard deviation of (0.812). And that there is an effect of sustainable leadership as a mediating variable, the standard value of the regression weight was (.146). In light of the results, the study presented a number of recommendations, the most prominent of which are: encouraging university employees to contribute to presenting innovative ideas and benefiting from them in improving the level of the university’s organizational reputation. Working to facilitate administrative procedures that ensure that faculty members and students obtain patents easily and without procedural complications.
Keywords: Sustainable Leadership; University Reputation; Organizational Ambidexterity